Delaying the Inevitable: Interest Rate Defense and Balance of Payments Crises - Lahiri, Amartya; Végh, Carlos A. (Journal of Political Economy, 2003)
The classical model of balance of payments crises implicitly assumes that the central bank sits passively as international reserves dwindle. In practice, however, central banks typically defend pegs aggressively by raising short‐term interest rates. This paper analyzes the feasibility and optimality of raising interest rates to delay a potential BOP crisis. Interest rate policy works through two distinct channels. By raising demand for domestic, interest‐bearing liquid assets, higher interest rates tend to delay the crisis. Higher interest rates, however, increase public debt service and imply higher future inflation, which tends to bring forward the crisis. We show that, under certain conditions, it is feasible to delay the crisis, but raising interest rates beyond a certain point may actually hasten the crisis. A similar nonmonotonic relationship emerges between welfare and the increase in interest rates. It is thus optimal to engage in some active interest rate defense but only up to a certain point. In fact, there is a whole range of interest rate increases for which it is feasible to delay the crisis but not optimal to do so.